The Role of Parents in Problematic Internet Use among US Adolescents - Bleakley, Amy (2016)
The internet has transformed the way youth communicate, learn, and network, with implications for their broader social, psychological, and physical health and well-being. With the technological capability of accessing the internet from anywhere, at any time, paired with the enormous variety of internet activities in which youth engage—from social networking to chatting to streaming videos to playing games to watching television content—instances of problematic internet behavior have emerged. We conducted an online national survey of 629 US adolescents ages 12–17 years old and a matching survey of one of their parents. We investigated the relationship between problematic internet behavior and parental monitoring, parental mediation of internet use, and parental estimates of their adolescent’s time spent using computers. Analyses showed that problematic internet use was associated with less parental monitoring and parental mediation and poorer parental relationships. Adolescents that spent a lot of time on the computer were also more likely to engage in problematic internet use. Although we cannot determine the direction of the relationships, results support the important role of parents in adolescents’ problematic internet use.